Legal Appropriation and Geopolitics of Madagascar's Continental Shelf for Sustainable Development - Mbola Mampiray Miandrito; Razafitahindraza Erica Feyzine Sulla (ite ngabdi, 2026)
This study examines the legal appropriation and territoriality of Madagascar's continental shelf as strategic instruments for sustainable development in southern Madagascar within the contemporary geopolitical context of the Indian Ocean. Grounded in the legal framework established by the United Nations Convention on the Law of the Sea (UNCLOS), the research explores how sovereign rights over marine resources may contribute to economic development, environmental protection, and maritime governance. Adopting a qualitative and interdisciplinary approach, the study combines doctrinal legal analysis, documentary research, and semi-structured interviews with stakeholders involved in maritime governance. The findings highlight that the Malagasy continental shelf constitutes both a legal and geopolitical asset capable of strengthening maritime sovereignty, promoting the sustainable exploitation of fisheries, energy, and marine resources, and enhancing regional cooperation. However, the effectiveness of legal appropriation remains closely linked to institutional capacities, integrated maritime governance, and ecosystem-based resource management. The study further demonstrates that sustainable development objectives can only be achieved through the articulation of functional sovereignty, environmental stewardship, maritime security, and the equitable inclusion of coastal communities. Madagascar's continental shelf therefore represents a strategic lever for fostering inclusive and sustainable maritime development in southern Madagascar.